Diet and the risk of head and neck cancer: a pooled analysis in the INHANCE consortium - Chuang, Shu-Chun; Ramroth, Heribert; Brenner, Hermann; Müller, Heiko (Cancer causes & control, 2012)
We investigated the association between diet and head and neck cancer (HNC) risk using data from the International Head and Neck Cancer Epidemiology (INHANCE) consortium. The INHANCE pooled data included 22 case-control studies with 14,520 cases and 22,737 controls. Center-specific quartiles among the controls were used for food groups, and frequencies per week were used for single food items. A dietary pattern score combining high fruit and vegetable intake and low red meat intake was created. Odds ratios (OR) and 95% confidence intervals (CI) for the dietary items on the risk of HNC were estimated with a two-stage random-effects logistic regression model. An inverse association was observed for higher-frequency intake of fruit (4th vs. 1st quartile OR = 0.52, 95% CI = 0.43-0.62, p trend < 0.01) and vegetables (OR = 0.66, 95% CI = 0.49-0.90, p trend = 0.01). Intake of red meat (OR = 1.40, 95% CI = 1.13-1.74, p trend = 0.13) and processed meat (OR = 1.37, 95% CI = 1.14-1.65, p trend < 0.01) was positively associated with HNC risk. Higher dietary pattern scores, reflecting high fruit/vegetable and low red meat intake, were associated with reduced HNC risk (per score increment OR = 0.90, 95% CI = 0.84-0.97).